Public Awareness of the Importance of Education in Segara Katon Village, Gangga District, North Lombok Regency - Lestari, Mawaddah; Apriawan, Andika; Rahmadi, Didin Septa; Mawardi, Taufik; Yorman (International Journal of Social Sciences and Humanities, 2023)
This study aims to describe the perspective of the Segara Katon village community, Gangga District, North Lombok Regency on the importance of education for them. The approach in this study uses a descriptive method with a qualitative approach. This study provides a description and explanation of the conditions or symptoms faced. . Data collection techniques in this study use three types of techniques, namely observation, interviews, documentation. Descriptive qualitative research is declared valid if there is no difference between the reported data and what actually happens to the object being studied. The results of the study explain that educational awareness in Segara Katon village, the community does not prioritize education because they do not know the importance of education for survival. There are at least two factors that influence the level of awareness of the Segara Katon village community towards education, namely external factors and internal factors. External factors that influence include economic factors (economic limitations), family factors (support in the family), and environmental factors (social situations of the community). While internal factors are related to the motivation of the community itself to carry out education.